Work motivation : history, theory, research, and practice - Latham, Gary P. (Thousand Oaks, Calif. : Sage Publications, 2012)
"Work Motivation: History, Theory, Research, and Practice provides unique behavioral science frameworks for motivating employees in organizational settings. Drawing upon his experiences as a staff psychologist in and consultant to organizations, author Gary P. Latham has written this book in a "mentor voice" that is highly personal and rich in examples, including enduring influences of mentors on researchers in the field."--BOOK JACKET.
Introduction : thirteen critical incidents in the life of a scientist/practitioner -- Pt. I. The 20th century : understanding the past -- Ch. 1. 1900-1925 : biology, behavior, and money -- Ch. 2. 1925-1950 : Dust Bowl empiricism -- Ch. 3. 1950-1975 : the emergence of theory -- Ch. 4. 1975-2000 : the employee is immersed in thought -- Ch. 5. 20th-century controversies -- Pt. II. The 21st century : examining the present 2000-2005 -- Ch. 6. Needs : the starting point of motivation -- Ch. 7. Personality traits : distal predictors of motivation -- Ch. 8. Values : trans-situational goals -- Ch. 9. Cognition : goals, feedback, and self-regulation -- Ch. 10. Social cognitive theory -- Ch. 11. Affect/emotion : the employee has feelings too -- Pt. III. Future directions and potential misdirections -- Ch. 12. Boundaryless psychology -- Pt. IV. Epilogue -- Ch. 13. The art of practice.
Includes bibliographical references (p. 281-320) and index.
Keywords: Employee motivation